Evaluation of the performance between post process kinematic and static technique in the forest environment : Procjena uspješnosti postprocesne kinematičke i statičke tehnike u šumskom okruženju - Pirti, Atinç (Array, 2021)
A GNSS involves a constellation of satellites orbiting Earth, continuously transmitting signals that enable users to determine their three-dimensional (3D) position with global coverage. The positioning principle is based on solving an elemental geometric problem, involving the distances (ranges) of a user to a set of at least 4-5 GNSS satellites with known coordinates. These ranges and satellite coordinates are determined by the user’s receiver using signals and navigation data transmitted by the satellites; the resulting user coordinates can be computed to an accuracy of several metres. However, centimetre-level positioning can be achieved using more advanced techniques (kinematic). GPS/GLONASS technique is becoming compulsory for many applications concerning forest management and inventory. This paper aims to comparing the coordinates resulted from Post Process Kinematic with the resulted coordinates for the same points resulted from static technique. Nonetheless, it appears that forest measurements with ± 1 cm accuracy cannot be guaranteed on all occasions, since difficult situations may lead to greater errors (about ±10 cm accuracy for horizontal components and about ± (20-100) cm accuracy for vertical components).